SECURITIZING SOUND HOREG: MUSIC, MORALITY, AND RELIGIOUS AUTHORITY IN INDONESIA - Pradana, Hafid Adim (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This article analyzes the haram fatwa issued by the Majelis Ulama Indonesia (MUI) East Java against the practice of Sound Horeg through a securitization theory approach. Sound Horeg, as a popular entertainment form in rural and semi-urban areas of East Java, has become a subject of social and moral controversy due to its content and social impact. The promulgation of the haram fatwa by MUI East Java in July 2025 marks a crucial point in the effort to frame this cultural practice as a threat to Islamic values and social order. Through the lens of securitization theory and a critical discourse analysis of the fatwa text and public sentiment data obtained using Brandwatch tools, this article demonstrates that the haram fatwa functions as a securitizing speech act—a discursive action that shifts Sound Horeg from a cultural domain to an existential threat. The main findings of this study indicate that despite initial public resistance, especially from youth and cultural communities, public opinion gradually shifted towards acceptance over time. This suggests that the success of securitization by non-state actors like MUI heavily relies on the dynamics of discourse, moral legitimacy, and underlying social structural support.